Menumbuhkan Cinta Al-Qur’an Sejak Dini melalui Program Tahfiz Berbasis Masjid di Desa Jorong Gando, Nagari Piobang - Ade Muhammad Ritonga; Najib Rahmatullah; Rafif Taufiqul Hakim (As-sunnah: Jurnal Pengabdian Masyarakat, 2026)
Low interest and limited ability in reciting and memorizing the Qur’an among young children remain a persistent challenge in community-based religious education. This condition was also found in Jorong Gando, Nagari Piobang, where Tawakkal Mosque serves as a learning site for children who have not yet learned to read fluently and who struggle to memorize. This community service activity aimed to nurture love for the Qur’an from an early age through a mosque-based tahfiz (memorization) program built on the Service Learning approach. Service Learning was carried out through planning, implementation, and reflection stages that actively involved KKNT (Thematic Community Service) students as learning companions. Activities comprised tahfiz coaching, recitation correction (tahsin), and structured memorization mentoring within the mosque environment. Quantitatively, 12 of the 30 enrolled children reached their memorization targets; qualitatively, the children’s Qur’anic recitation improved markedly. Although the program faced challenges such as inconsistent attendance and uneven memorization ability among participants, solutions implemented through parental outreach and ability-based grouping proved effective. The mosque-based tahfiz program delivered through Service Learning is thus shown to have a positive effect on both children’s Qur’anic competence and their affective attachment to the Qur’an from an early age. Beyond its immediate outcomes for the children involved, the activity also illustrates how a Service Learning placement can build the pedagogical competence of the accompanying university students, suggesting that mosque-based tahfiz programs of this kind merit wider adoption as a standard KKNT placement model in similarly under-resourced village settings.